Benefits and Risks of Financial Globalization : Challenges for Developing Countries - Schmukler, Sergio L. (Federal Reserve Bank of Atlanta, 2013)
This paper discusses the benefits and risks that financial globalization entails for developing countries. Financial globalization can lead to large benefits, particularly to the development of the financial system. But financial globalization can also come with crises and contagion. The net effect of financial globalization is likely positive in the long run, with risks being more prevalent right after countries liberalize. So far, only some countries, sectors, and firms have taken advantage of globalization. As financial systems turn global, governments lose policy instruments, so there is an increasing scope for some form of international financial policy cooperation.